2004
DOI: 10.1088/1009-0630/6/5/009
|View full text |Cite
|
Sign up to set email alerts
|

Unfiltered Diesel Engine Exhaust Treatment by Discharge Plasma: Effect of Soot Oxidation

Abstract: A cascaded system of electrical discharges (Non-thermal plasma), catalyst and adsorption process was investigated for the removal of oxides of nitrogen (NO,) and carbon monoxide (CO) from a Diesel engine raw exhaust. The three processes were separately studied first, and then the cascaded processes. namely plasma-catalyst and plasma-adsorbent, were investigated. In this paper main emphasis was laid on the effect of carbonaceous soot oxidation on the plasma treatment process. While the cascaded plasma-catalyst … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Some researchers combined plasma with other technologies to realize controlling of NO x [4][5][6]. In the late 1990s, Penetrante et al [7][8] suggested that in the presence of hydrocarbons as reductants, two-stage process consisting of plasma pretreatment of the exhaust before flow over a lean NO x catalyst could improve NO x removal obviously in contrast with either plasma or SCR alone, which confirmed by their experiments.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some researchers combined plasma with other technologies to realize controlling of NO x [4][5][6]. In the late 1990s, Penetrante et al [7][8] suggested that in the presence of hydrocarbons as reductants, two-stage process consisting of plasma pretreatment of the exhaust before flow over a lean NO x catalyst could improve NO x removal obviously in contrast with either plasma or SCR alone, which confirmed by their experiments.…”
Section: Introductionmentioning
confidence: 93%
“…Different hydrocarbons including C 2 H 4 , C 3 H 6 and CH 4 have been added into the simulated exhaust gas as reductants, and the performance of NO x removal were investigated over various catalysts in combination with plasma pretreatment [6,[9][10][11][12][13], such as In/Al 2 O 3 , γ -Al 2 O 3 , V 2 O 5 /TiO 2 , NaY, and primary reaction mechanism was also studied. Results showed that PF-SCR could arrive at much higher NO x removal rate than plasma alone, and most of removed NO x could be converted to N 2 over certain catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the presence of carbonaceous soot in the diesel exhaust gas changes the reaction, as the NO-NO 2 conversion is less probable. In this case, the O/OH radicals are consumed; however, NO 2 can react with soot [69] (see also discussion below). The most efficient way is the application of a plasma reactor along with an additional catalyst reactor.…”
Section: Plasma Utilization For Pollutant Removal In Flue Gasmentioning
confidence: 99%
“…Rajanikanth et al [9][10][11][12][13] reported a series of studies examining the de-NO x efficiency of a stationary 4.4 kW diesel engine exhaust at no load and 50% load conditions, using NTPcatalyst or adsorbent processes. The filtered exhaust before the after-treatment system included NO, NO 2 , CO, hydrocarbons, aldehydes and CO 2 .…”
Section: Hydrocarbon-selective Catalytic Reduction Using Non-thermal Plasmamentioning
confidence: 99%